The Impact of Music on Networking and Education - Rojc, Maja; Matjašič, Tilen; Kržič, Marta (Celovita pot izobraževanja: Od ideje do mreženja, 2026)
The chapter examines the influence of background music on educational events, with a focus on learning, the overall event experience and networking among participants. The purpose of the work is to determine in which parts of a professional educational event music is appropriate, when it may become distracting and how it can be planned as a supportive element of the event. The empirical part is based on data collected through a survey of participants in professional education programmes and an interview with the organiser. The results show that participants support the use of music most strongly upon arrival, during breaks, during networking and at the end of the event, while they generally prefer silence during lectures. Quiet instrumental or ambient music appears to be the most suitable, as it does not interfere with speech or distract attention from the content. The findings confirm that music does not serve merely as decoration for the event, but as an important element of the sound environment that must be planned according to the purpose of each phase of the programme. Thoughtful use of music can contribute to a better participant experience, greater social relaxation and a more professional delivery of the educational event.